Mapping the international knowledge base of educational leadership, administration and management: a topographical perspective. Issue 1 (2nd January 2021) - Tian, Meng; Huber, Stephan Gerhard
ABSTRACT: This study mapped the international knowledge base of educational leadership, administration and management (EdLAM) from a topographical perspective. Altogether 1651 publications from 18 peer-reviewed English journals published between 2007 and 2016 were reviewed. Combining bibliometric and content analyses, the authors identified 55 countries and regions that produced EdLAM publications. About half the publications came from five Anglo-Saxon countries, a quarter from Europe and a quarter from four emerging regions (Asia, the Middle East, Africa and Latin America). In each cluster of countries, key EdLAM research themes were identified and illustrated with reviewed literature. The overall development trends of EdLAM research include the continuous theorisation and empirical investigation of EdLAM, the increasing critical voices against Neoliberalism and the New Public Management in education, the growing awareness of contextualising EdLAM research locally, and the rising value of comparative studies.